What Do We Know About NYC’s Stop and Frisk Program?: A Spatial and Statistical Analysis - Evans, Douglas; Maragh, Cynthia-Lee; Porter, Jeremy (Advances in Social Sciences Research Journal, 2014)
Since its inception, New York City's stop-and-frisk program has been controversial. The policy allows police officers to stop, question, and frisk individuals who are suspected of committing, having committed or about to commit a crime. Advocates of this policy contend that its purpose is to protect civilians and police officers, as it enables officers to detain persons that they believe are in possession of unlawfully concealed weapons. Critics maintain that the practice violates civil rights and leads to racial profiling. Limited research has moved beyond these types of descriptive examinations of the Stop and Frisk data. Our project employs data from the U.S. Census Bureau and the New York Civil Liberties Union on 2011 NYPD stops and frisks. In moving beyond the descriptive stage, this research utilizes a spatially centered analytical approach to measure and identify geographic clusters of high Stop and Frisk rates across New York City police precincts and subsequent spatial regression to link variations in those rates to community level characteristics. Results indicate both significant spatial clusters of high rates of race-specific stops and a series of statistically significant relationships of those variations to similar variations in explanatory variables.